Various types of Alopecia and the options of the treatment - Hlail, Afrah Thiab (AL-Kindy College Medical Journal, 2020)
Alopecia (Baldness) is very usual trouble in current time. It is accompanied by an intensive weakening of the scalp’s hair and follows a specific pattern. Hereditary predisposition plays a very important role in alopecia despite not completely understood. Alopecia can be typed to various categories according to etiology, may be due to hereditary factors, autoimmune disease, and drugs or chemicals. There are many options of strategies of treatment according to the type and causes of alopecia. Chemical or synthetic medications apply for the management of hair loss are accompanied by a wide range of undesirable effects. Naturally occurring drugs also play important role in alopecia management with minimal side effects.